2021
DOI: 10.1136/bmjdrc-2021-002427
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c in combination with fasting plasma glucose trumps fasting plasma glucose alone as predictive indicators for diabetes mellitus: an ambidirectional cohort study of Thai people with impaired fasting glucose

Abstract: IntroductionThis ambidirectional cohort study aimed to assess the performance of combining hemoglobin A1c (HbA1c) to fasting plasma glucose (FPG) for estimation of progression rate to diabetes mellitus (DM) and to explore the risk factors of DM in patients with impaired fasting glucose (IFG).Research design and methodsPatients with IFG were eligible for this study. IFG was defined as FPG of 100–125 mg/dL. Progression rates to DM were estimated using Kaplan-Meier analysis. Risk factors of DM were explored by Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A superiority trial approach utilizing a one-way analysis of variance method was applied for estimating the sample size. The baseline mean and standard deviation (SD) of FPG in the prediabetes cohort were 105 and 9 mg/dL, respectively [26]. We anticipated that receiving TRE plus BE, and TRE alone would lead to a reduction in the FPG of approximately 7% and 5%, respectively, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A superiority trial approach utilizing a one-way analysis of variance method was applied for estimating the sample size. The baseline mean and standard deviation (SD) of FPG in the prediabetes cohort were 105 and 9 mg/dL, respectively [26]. We anticipated that receiving TRE plus BE, and TRE alone would lead to a reduction in the FPG of approximately 7% and 5%, respectively, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the previously mentioned Thai studies only provided information on DM incidence in the low-to moderate-risk population with prediabetes. ( Thamakaison et al, 2021 ; Wutthisathapornchai A 2021 ) In addition, the analyses drew on an extensive study sample.…”
Section: Discussionmentioning
confidence: 99%
“…An ambidirectional cohort study indicated that patients with both high FPG and abnormal HbA1c are at a higher risk of developing T2DM, while HbA1c in combination with FPG may help distinguish the subgroups with the highest risk of diabetes in people with impaired fasting glucose. 9,40 Elevated FPG levels are associated with lower insulin response and sensitivity and are related to an increased incidence of T2DM. 41 To the best of our knowledge, this is the first nomogram to predict incident T2DM in obese patients with abdominal obesity, using a standardized lifestyle factor questionnaire.…”
Section: Discussionmentioning
confidence: 99%